Application of Multiple Representation-Based VIFOCA Problem Solving Strategies in Physics Learning - Napis; Yufiarti; R.A. Murti Kusuma Wirasti (Universitas Pendidikan Ganesha, 2023)
Students' difficulties in solving physics problems were identified from various factors, including students' poor understanding of how to apply the steps of a physics problem solving strategy. Therefore, it is necessary to innovate strategies which both simple and easy to use by students in the process of solving physics problems by conducting literature reviews. The study aimed at analyzing multiple representation-based vifoca problem solving strategies in physics learning. This research used mixed methods, literature study with meta-analysis using 22 research subjects from national journals, Sinta-accredited national journals, AIP Conference, and articles from Scopus-indexed international journals in the 2018-2022 range. The survey of 82 respondents including lecturers and students, were used to determine the responses to the application of physics problem solving strategies. The literature study shows the formulation of a physics problem solving strategy that is named VIFOCA, which consists of three work steps, namely: (1) visualization, (2) formulation, and (3) calculation. Positive responses based on survey results showed that the VIFOCA strategy can be used to solve physics problems, the work steps are systematic, easy to apply, and more practical. VIFOCA strategy follow-up studies can be carried out in a comprehensive manner that is empirically applied in physics learning to determine the effectiveness of the VIFOCA strategy in solving physics problems.